PERSEPSI MASYARAKAT DUSUN GERUPUK TERHADAP PENGEMBANGAN PANTAI GERUPUK SEBAGAI DAYA TARIK WISATA - Sirojuddin, Maisum; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 2 No 1 (2014): VOL 2, NO 1 (2014): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Gerupuk Beach is one tourist attraction that its existence has been known as a tourist activity surf because the waves were very large throughout the season and the beauty of white sandy beaches, as well as its strategic location as a potential capital to be developed into a tourist attraction in Central Lombok. This study was conducted aimed to determine the perceptions of society towards the development of coastal hamlet Gerupuk Gerupuk as a tourist attraction. Data collected through observation, interviews, and questionnaires, literature study. Sampling technique used is proportional random sampling and accidental sampling of data that have been collected then analyzed using qualitative descriptive analysis. Based on the results of the study, found that public perception towards the development of coastal hamlet Gerupuk Gerupuk average member of the responses strongly agree, because people realize and feel that to develop tourism in the area will provide many positive benefits for the future, such as economic growth, preservation of natural and cultural in the region.
Keywords: Keywords : public perception, coastal development Gerupuk